Synthesis of templated carbons starting from clay and clay‐derived zeolites for hydrogen storage applications. (13th October 2014) - Musyoka, N. M.; Ren, J.; Langmi, H. W.; Rogers, D. E. C.; North, B. C.; Mathe, M.; Bessarabov, D.
Summary: Clay and its recrystallized zeolitic derivatives were used in this study as templating agents for carbon nanostructured materials. The conventional nanocasting process that involves impregnation with furfural alcohol and subsequent chemical vapour deposition was followed. Several techniques such as X‐ray diffraction (XRD), scanning electron microscopy (SEM), thermo‐gravimetric analysis (TGA) and surface area analysis were used to characterize the parent templating materials including the resulting nanocasted carbons. The study demonstrated that there is greater potential for the use of value‐added clays rather than their pristine form and hence presents a cost‐effective alternative for producing carbonaceous materials with more attractive properties for hydrogen storage applications. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The study compared the use of clays and value‐added clays for hydrogen storage applications. Zeolite templated carbons had a higher hydrogen uptake than clay templated carbon. Independent optimization for different clays and respective derivatives were recommended.